Echinobothrium harfordi sp. nov. (Cestoda: Diphyllidae) from Raja naevus in the North Sea and English Channel - McVicar, A. H. (Journal of Helminthology, 1976)
Echinobothrium harfordi sp. nov. from the spiral intestine of Raja naevus in British waters is described and illustrated. The species most closely resembles E. affine as both possess two groups of eleven large apical hooks, but can be distinguished by fewer peduncle spines and by characteristics of the eggs. The intensity of infection in individual hosts was generally low, and although the incidence of infection was high in rays less than 35 cm in length, this fell towards zero in larger rays. The cestode showed a marked affinity for the first two tiers of the spiral intestine.